Adherence to Oral Administration of Endocrine Treatment in Patients With Breast Cancer: A Qualitative Study. Issue 1 (January 2018) - Iacorossi, Laura; Gambalunga, Francesca; Fabi, Alessandra; Giannarelli, Diana; Marchetti, Anna; Piredda, Michela; De Marinis, Maria Grazia
Abstract : Background: Breast cancer is the most common cancer in women in the world, and it is also the leading cause of cancer deaths among women. Nevertheless, breast cancer survival has increased as a result of improvements in early diagnosis and therapy, for example, oral endocrine therapy. Despite the importance of adherence to endocrine therapy, its trend appears complex and multidimensional and therefore has many loopholes and missing information. Objective: The study aims to explore the experiences of adherence to endocrine therapy in women with breast cancer and their perceptions of the challenges they face in adhering to their medication prescribed. Methods: The study used a qualitative exploratory design, with face-to-face semistructured interviews. Data were analyzed using framework analysis in accordance with Ritchie and Spencer's approach. Results: The sample included 27 women. Seven themes were identified: the different faces of adherence, fear of the drug, adherence stimulates the balance of the experience of illness, adherence influences the future of disease, adherence requires attention to the person, knowledge seeking, and "forgetfulness" activates the search for functional strategies. Conclusions: This study shows that adherence assumes different connotations that are mainly influenced by the type of relationship established with health professionals the attention paid to the person, the information received, and the influence that the drug has on the disease. Implications for Practice: It appears that fear has a strong influence on the behaviors involved in taking the therapy. The only way to overcome irrational fear is to improve the patient's knowledge.